COMPARISON STUDY OF BIM MODELING IN SEISMIC ANALYSIS FOR DIFFERENT BUILDING FUNCTIONS BASED ON SNI 1726:2019: english - Asri Puspita Sari Sidabutar; Jessica Sjah; Ayomi Dita Rarasati (LPPM Universitas Abdurrab, 2024)
The application of BIM in Indonesia in building planning which refers to SNI 1726:2019 is still very minimal. This research involves two different types of buildings, namely hotel buildings and hospitals. The modeling used is simple concrete building structure modeling with variations of 3, 9 and 12 floors in Revit as a model. The same BIM model is used in the Structural Analysis Robot and then the results of the two buildings are compared, namely the comparison of story shear and story displacement. The research methods used are data collection, BIM modeling using the latest software, and seismic analysis taking into account the parameters described in SNI 1726:2019. The results of BIM modeling and seismic analysis were then compared for both types of buildings.